The battle for world wide web dominance: In search of network externalities - Veera Bhatiasevi (2018)
The purpose of this study is to test for the existence of network externalities and to identify possible sources of network externalities in the 3 leading search engine and web-based email providers namely Google, Microsoft and Yahoo. A product creates direct network externalities when the utility that an agent derives from consuming the product increases with the number of other agents consuming the same product. When a market exhibits network externalities, winner takes all or winner takes most is usually the consequence. Data was collected from 449 university students in Thailand. Participants completed a 20 question survey conducted by trained administrators. The binary logit model was applied to test for the adoption and network externalities in or with respect to search engines and web-based email. The study indicates that network externalities do not exist in the selection of a search engine. Google is chosen because of two factors, its features and reputation. The results show that the only web-based email service that exhibits traits of network externalities is Hotmail, the market leader. This means that users choose Hotmail as their primary web-based email because others are also using it. Recommendation by others is not the source of network externalities for web-based email. The study provides an enhanced understanding of how firms dominate and sustain their lead in the world wide web. Furthermore, this research also helps us to understand future trends in the cyber world. A limitation of this study is that other services such as Google talk, Windows Live Messenger and Yahoo Messenger were not considered in measuring network externalities. Thus, future research could usefully include these services. Although the topic of network externalities has been studied previously, this is the first that attempts to identify the traits of network externalities in the search engine and web-based email market. © Medwell Journals, 2011.